Double-layered radar absorbing structures of MnZn ferrite/Pani-coated MWCNT filled nanocomposites for X-band frequencies. (3rd July 2022) - Haritha, T.; Ramji, K.
ABSTRACT: In this study, radar absorbing structures (RAS) containing MnZn ferrite/Polyaniline (Pani) coated multi-walled carbon nanotubes (PCNTs) were fabricated to observe their microwave absorption behaviour in X-band frequency range. The ferrite nano particles were prepared by sol–gel auto combustion method. The prepared nano ferrite powder was characterised using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and vibrating sample magnetometer (VSM). RAS filled with nano ferrite particles and PCNTs in different concentrations were fabricated to investigate their microwave absorption behaviour using a vector network analyzer (VNA) and later reflection loss (RL) is estimated. The minimum RL loss estimated for double-layered RAS are found to be −29.06 dB at 10.8 GHz for ferrite fixed samples and −33.07 dB at 9.6 GHz for PCNT fixed samples. Further, their mechanical behaviour is examined.